Antimicrobial peptides provide wider coverage for targeting drug‐resistant bacterial pathogens. Issue 2 (1st October 2021) - Amiss, Anna S.; Henriques, Sónia Troeira; Lawrence, Nicole
Abstract: We need new treatment options to control bacterial infections. Bacteria use several strategies to resist drug treatment, including modification of the drug target, and adaptation to a different lifestyle, such as intracellular niches within host cells. Drugs that act on diverse targets are less likely to induce resistance in bacteria, than current antibiotics acting on a single molecular target. Antimicrobial peptides have been explored as a new class of antibiotics because they selectively kill bacteria via a mechanism that involves recognition of the negatively charged microbial surface. Furthermore, antimicrobial peptides with cell‐penetrating properties can cross host cell membranes and target bacteria in the cytosol or sequestered in vesicles. Therefore, bacteria in intracellular niches are less capable of evading treatment and the likelihood of establishing drug resistance is further reduced. This review highlights the potential of antimicrobial peptides as alternative therapeutics to target bacterial pathogens in both extracellular and intracellular environments, and to avoid acquired drug‐resistance. Abstract :